South African treason trials - Adams, Farrid (Photographed for [Cooperative Africana Microform Project of the] Center for Research Libraries by Dept. of Photoduplication, the University of Chicago, 1965)
Transcript of pp. 1-24893 of the trial for treason against Farrid Adams (variants: Farid and Faried) and others brought by the South African government, August 3, 1959 - March 23, 1961.